2002
DOI: 10.1002/biof.5520160302
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effects of tetrahydro‐β‐carboline derivatives identified in aged garlic extract

Abstract: 1,2,3,4-Tetrahydro-beta-carboline derivatives (THbetaCs) are formed through Pictet-Spengler chemical condensation between tryptophan and aldehydes during food production, storage and processing. In the present study, in order to identify the antioxidants in aged garlic extract (AGE), we fractionated it and identified four THbetaCs; 1-methyl-1,2,3,4-tetrahydro-beta-carboline-3-carboxylic acids (MTCC) and 1-methyl-1,2,3,4-tetrahydro-beta-carboline-1,3-dicarboxylic acid (MTCdiC) in both diastereoisomers using liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 33 publications
0
41
0
1
Order By: Relevance
“…Using liquid chromatography–mass spectrometry (LC–MS), NMR, and hydrogen peroxide scavenging assay, Ichikawa et al. () identified alkaloids with significant antioxidant activity in an aged garlic extract: 1‐methyl‐1,2,3,4‐tetrahydro‐β‐carboline‐3‐carboxylic acids (MTCC) and 1‐methyl‐1,2,3,4‐tetrahydro‐β‐carboline‐1,3‐dicarboxylic acid (MTCdiC) diastereoisomers (as shown in Figure ). Sato, Kohno, and Niwano () reported that the contents of (1R, 3S)‐MTCC and (1S, 3S)‐MTCC in BG increased significantly after spontaneous fermentation at 60 to 70 °C and 85% to 95% relative humidity for 40 days, compared with those in FG (trace amounts).…”
Section: Characteristic Components and Their Formation Mechanisms In Bgmentioning
confidence: 99%
See 1 more Smart Citation
“…Using liquid chromatography–mass spectrometry (LC–MS), NMR, and hydrogen peroxide scavenging assay, Ichikawa et al. () identified alkaloids with significant antioxidant activity in an aged garlic extract: 1‐methyl‐1,2,3,4‐tetrahydro‐β‐carboline‐3‐carboxylic acids (MTCC) and 1‐methyl‐1,2,3,4‐tetrahydro‐β‐carboline‐1,3‐dicarboxylic acid (MTCdiC) diastereoisomers (as shown in Figure ). Sato, Kohno, and Niwano () reported that the contents of (1R, 3S)‐MTCC and (1S, 3S)‐MTCC in BG increased significantly after spontaneous fermentation at 60 to 70 °C and 85% to 95% relative humidity for 40 days, compared with those in FG (trace amounts).…”
Section: Characteristic Components and Their Formation Mechanisms In Bgmentioning
confidence: 99%
“…The initial content of -carbolines in FG is mostly very low, but aging (for example, in aqueous ethanol, at room temperature, for 4 to 10 months) and thermal treatment (for example, 60 to 90 • C for 10 to 70 days) of FG can significantly increase the content of 1-methyl-1,2,3,4-tetrahydro--carboline derivatives (TH Cs), causing an increase in the hydrogen peroxide scavenging activity (Ichikawa et al, 2006). Using liquid chromatography-mass spectrometry (LC-MS), NMR, and hydrogen peroxide scavenging assay, Ichikawa et al (2002) identified alkaloids with significant antioxidant activity in an aged garlic extract: 1-methyl-1,2,3,4-tetrahydro-carboline-3-carboxylic acids (MTCC) and 1-methyl-1,2,3,4tetrahydro--carboline-1,3-dicarboxylic acid (MTCdiC) diastereoisomers (as shown in Figure 2). reported that the contents of (1R, 3S)-MTCC and (1S, 3S)-MTCC in BG increased significantly after spontaneous fermentation at 60 to 70 • C and 85% to 95% relative humidity for 40 days, compared with those in FG (trace amounts).…”
Section: Alkaloids (Organic Compounds Containing Basic Nitrogen Atoms)mentioning
confidence: 99%
“…Besides SAC, there are other compounds in AGE exhibiting antioxidant properties: (a) S-allylmercaptocysteine scavenges • OH and 1 O 2 [37]; (b) alliin scavenges • OH [38], O 2 •− [32], and H 2 O 2 [22] and inhibits lipid peroxidation [22]; (c) N α -(1-deoxy-D-fructos-1-yl)-L-arginine scavenges H 2 O 2 [8, 39] and also inhibits the Cu 2+ -induced low-density lipoprotein (LDL) oxidation and peroxides release during the coincubation of macrophages with oxidized LDL [39]; (d) tetrahydro-beta-carbolines show a strong H 2 O 2 scavenging activity while inhibit 2,2′-azobis(2-amidinopropane) hydrochloride-induced lipid peroxidation and nitrite production induced by lipopolysaccharide in murine macrophages [9, 10]. …”
Section: Antioxidant Mechanisms Associated With the Protective Effmentioning
confidence: 99%
“…The effectiveness of garlic has been related to its potent antioxidant properties [87] [88] [89]. Several studies were done on the health benefits of garlic, usually stated its sulfur containing metabolites as allicin and its derivatives.…”
Section: Experimental Studymentioning
confidence: 99%